Implementation Of The Pancasila Student Profile Strenghening Project (P5) In The Independent Curriculum In High Schools - Ritagustiani Ritagustiani; Erianjoni Erianjoni; Junaidi Indrawadi; Eka Asih Febriani (Dinasti Publisher, 2025)
The purpose of this study is to provide an overview of the successful implementation of the Pancasila Student Profile Strengthening Project (P5) in Senior High Schools through a literature review of several related articles. The research method used is library research by accessing the Google Scholar database using the keywords